2013
DOI: 10.1371/journal.pone.0068998
|View full text |Cite
|
Sign up to set email alerts
|

Localized Retinal Nerve Fiber Layer Defects Detected by Optical Coherence Tomography: The Beijing Eye Study

Abstract: ObjectiveTo assess the prevalence of localized retinal nerve fiber layer defects (LRNFLD) and associated factors in adult Chinese.MethodsThe population-based Beijing Eye Study 2011 included 3468 individuals (mean age: 64.6±9.8 years (range: 50–93 years)). The study participants underwent a detailed ophthalmological examination including spectral-domain optical coherence tomography (SpectralisR-OCT) assisted measurement of the RNFL. A LRNFLD was defined as a sector in which the RNFL contour line dipped into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
0
22
0
2
Order By: Relevance
“…In a similar manner, the other longitudinal population-based studies in ophthalmology have not yet presented such data and findings. 9,17,[30][31][32] Other recent studies by the Beijing Eye Study, such as the observed association between the estimated cerebrospinal fluid pressure and retinal vein diameter in arterial hypertension, and the 10-year mortality of ocular diseases, do not have a direct association with the topic of the current study. 33,34 From a practical point of view, one may raise the question whether brain imaging should be performed to exclude cerebral ischemic attacks in patients without glaucoma or diabetic retinopathy and who present with an incident RNFLD.…”
Section: Discussionmentioning
confidence: 57%
“…In a similar manner, the other longitudinal population-based studies in ophthalmology have not yet presented such data and findings. 9,17,[30][31][32] Other recent studies by the Beijing Eye Study, such as the observed association between the estimated cerebrospinal fluid pressure and retinal vein diameter in arterial hypertension, and the 10-year mortality of ocular diseases, do not have a direct association with the topic of the current study. 33,34 From a practical point of view, one may raise the question whether brain imaging should be performed to exclude cerebral ischemic attacks in patients without glaucoma or diabetic retinopathy and who present with an incident RNFLD.…”
Section: Discussionmentioning
confidence: 57%
“…14 Many studies have demonstrated that, even in the absence of vascular changes, several layers in the retina and RNFL thickness around the optic disc become significantly thinner in eyes with type II diabetes compared with those without diabetes. 8,9 Our study demonstrated that average RNFL thickness and sector RNFL thickness in superior and inferior quadrants in diabetes were significantly thinner than those of nondiabetic, nonglaucomatous controls (Table 1).…”
Section: Discussionmentioning
confidence: 70%
“…Retinal nerve fiber layer (RNFL) abnormalities, manifesting as thinning or defects, are frequently encountered in subjects with diabetes. [3][4][5] Thinning of the RNFL around the optic disc and macula thinning have been reported, and these changes often occur before the development of DR. 3,[6][7][8][9] Retinal nerve fiber layer defects, first described by Hoyt et al 10 50 years ago, is one of the pathognomic findings in glaucomatous optic neuropathy. The RNFL defect may precede detectable changes on the optic disc and visual field (VF), 11 and RNFL-based assessments have been reported to be superior to optic disc-based assessments for the diagnosis of glaucoma.…”
mentioning
confidence: 99%
“…15,16 Because of unreliable RNFL measurements with respect to the detection of localized RNFLDs, 154 subjects were excluded, and data on previous stroke were not available for 150 additional subjects. Because glaucoma can lead to localized RNFLDs, we excluded all subjects (n=174) with glaucomatous optic neuropathy so that the study population provided by the Beijing Eye Study eventually included 2890 subjects (Table).…”
Section: Resultsmentioning
confidence: 99%
“…The Beijing Eye Study 2011 was a population-based cross-sectional study in Northern China and was described in detail previously. 15,16 Of an eligible population of 4403 individuals fulfilling the inclusion criterion of an age of 50+ years, 3468 (78.8%) individuals participated in the survey. The study design included an interview, a detailed ophthalmic examination, collecting of fasting blood samples, measurement of blood pressure, body height and weight, and spectral-domain OCT of the RNFL.…”
Section: Strokementioning
confidence: 99%